STUDI EKSEGETIS UNGKAPAN ”KUASAILAH DIRIMU DALAM SEGALA HAL” DALAM II TIMOTIUS 4:15A - Waharman Waharman (Manna Rafflesia, 2015)
In his letter the Apostle Paul reminded Timothy that evil and apostasy would increase, so Timothy needed self-control, in service. Self-mastery is very important in the life of a servant of God. Therefore through this exegetical study can help believers understand the principle of 'controlling oneself in all things' and applying it as the principle of serving life.